Análisis y mejoramiento del proceso de capacitación de los trabajadores en el área de talento humano del Instituto Ecuatoriano de Seguridad Social Matriz Nivel Quito - Larcos Caiza, Edison Javier (2018)
This topic talks about how to improve the process of training human resources. We get it adding a new way to identify which areas need training to have a high level of work performance. The main purpose of the project is to improve the training process from people who work in Human Resources. It through the right implementation of hard and soft competences to guarantee the process and systems of threads that are part of Human Resources department. The new alternative created to optimize and improve training was inspired in recollecting information about topics that has been used in several departments of Human Resources which are payroll, legal, recruitment, and training. In fact, improvements will help the different threads to maintain the high level of personal and work goals. The training process shows several topics to analyze. In addition, it is recommended to use these topics to optimize worker´s time. Also, this project will help collaborators to have general and specific ideas about the institution. As a result, these ideas will help to look for new ways to make faster and efficient process than today.